’n Regsteoretiese en funks ionele perspektief op die beste belange van die (minderjarige) kind - Fick, G. H. (Koers, 1991)
In most modern legal systems the principle of the child’s best interests is held to be the panacea for adjudication in cases of interference within an intact family unit or remediation whenever the family is split apart. But with the same conviction one has to say that the principle is not sofinely tuned. As a simple rule of decision it must be rejected , because its content oscillates between it being a (paramount?) consideration amongst others and it being a norm depicting and weighing competing interests (rights). It is the premise of this article that even though the principle is indeterminate it can be made meaningful as an explicit criterion (amongst others) for adjudication only in cases where the court has already intervened within a parent-child relationship and wishes to resolve the whole issue as efficaciously as possible. It is further suggested that the principle should not be applied when there is state intervention in an intact family unit. Under these circumstances the best inte re st of the child and the preservation of family life result in an undeniable paradox. The tension cannot be resolved by applying the superficially simple rule of decision, namely the child’s best interest. A more exact test needs to be applied to remove some of the anomalies and uncertainties of the well-known concept. The author of this article suggests an approach of a more delictual nature. The question needs to be answered at what stage does it become unlawful for parents to infringe upon their child’s (subjective) rights or breach their legal duties towards their child, justifying court intervention in the family unit. The (positive) law has not specifically determined this boundary of (objective) unreasonable conduct and one has to rely on indicia relevant to a particular case, in accordance with the convictions of the community, such as the special relationship between the parties, the particular conflicting interests of the parties, the motives of the parlies, and appropriate considerations of social policy. In this way the concept (of the child’s best interests) can be simplified and elucidated.